(untitled) (KASBIT Business Journal, 2025)
This study looks at waqf’s capacity to boost economies amid recessions brought on by crises. It provides an examination of the hypotheses put up by economists on the causes of recessions, focusing on elements like the distinction between the financial and genuine sectors and the impact of price speculation. The economic recessions of the 20th and 21st centuries are examined historically, emphasizing the enduring effects of slower economic expansion and activity. The research also explores the evolution of waqf in several nations, exposing notable asset values but constrained output. We discovered some waqf development models that provide paths forward and possible economic gains, such as more economic activity, better growth in the economy, price stability, higher productivity, lower unemployment, and less wealth inequality. Notwithstanding its potential, we discovered that waqf’s worldwide influence is still constrained because of poor management, insufficient administration, and an absence of government backing. The study emphasizes how crucial it is to have supporting regulations and efficient waqf administration to realize the full potential of this asset and promote global economic stability.